2021
DOI: 10.1002/jgh3.12656
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of early gastric cancer associated with autoimmune gastritis

Abstract: Background Autoimmune gastritis is known to be associated with neoplastic lesions but the relationship between autoimmunity and tumorigenesis have not been sufficiently clarified. The aim of this study is to assess the clinicopathological characteristics of gastric cancer cases associated with autoimmune gastritis. Methods A total of 24 patients diagnosed as early gastric cancer with autoimmune gastritis were registered. Chart reviews with the data including age, gender, state of Helicobacter pylori infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a Japanese cohort, the prevalence was 11.4% for type 1 neuroendocrine tumors and 9.8% for adenocarcinomas [56]. A distinct pattern was also observed in the distribution of tumors in patients with gastric cancer associated with autoimmune gastritis [62]. Regarding the spatial sites of gastric cancer, 28.1%, 53.1%, and 18.8% were located in the upper, middle, and lower regions, respectively.…”
Section: Risk Of Gastric Neoplasmmentioning
confidence: 85%
“…In a Japanese cohort, the prevalence was 11.4% for type 1 neuroendocrine tumors and 9.8% for adenocarcinomas [56]. A distinct pattern was also observed in the distribution of tumors in patients with gastric cancer associated with autoimmune gastritis [62]. Regarding the spatial sites of gastric cancer, 28.1%, 53.1%, and 18.8% were located in the upper, middle, and lower regions, respectively.…”
Section: Risk Of Gastric Neoplasmmentioning
confidence: 85%
“…A recent study reported a pooled annual gastric cancer incidence of 0.14% in autoimmune gastritis, with its overall relative risk for gastric cancer being 11.05 [ 12 ]. In addition, Kitamura et al characterized gastric cancers associated with autoimmune gastritis as protruded types, involving large tumor sizes, upper tumor locations, and papillary pathological types, with most of these being intramucosal [ 13 ]. The synchronous triple gastric cancers diagnosed in this case were shown to be consistent with the characteristics noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors contributing to the increase in AIG include the promotion of endoscopic screening; group D (negative for H. pylori and positive for pepsinogen [PG] [5]) findings in gastric cancer risk stratification tests; evaluation for macrocytic anemia [6], iron deficiency anemia, thyroid disease [7][8][9], and gastric cancer [10][11][12][13][14][15][16]; close examination of gastric neuroendocrine tumors (NETs) [17][18][19][20][21][22][23][24]; and the presence of AIG in a subset of repeat cases of H. pylori eradication by 13 C-urea breath test (UBT) [25]. Terao et al [26] retrospectively reviewed the clinical and endoscopic characteristics of 245 AIG cases collected from 11 institutions in Japan and showed that the best diagnostic indicators for AIG were endoscopic findings (31.2%), followed by macrocytic anemia (16.1%), and repeated H. pylori eradication due to 13 C-UBT false positivity (15.1%).…”
Section: Introductionmentioning
confidence: 99%